Digital transformation of higher medical education: Challenges, optimization - Makarenko, O.; Vainahii, O.; Tsybulska, T. E.; Koval, A.; Vivsyannuk, V.; Цибульська, Таміла Євгенівна (My University, 2023)
The purpose of the article is to analyze the digital transformation of higher medical education, trace individual challenges and methods of optimization to improve the pedagogical process. To realize this goal, a number of scientific methods are applied, including analysis, synthesis, deduction and induction, abstraction, and prognostic method. In the results, the aspects of the digitalization processes of the formation of the educational medical environment through the prism of optimization and the challenges on the way to improving the digitalization of higher medical education institutions of Ukraine are investigated. Certain difficulties have been noted on the way to the introduction of innovative technologies, which in Ukrainian realities are mostly related to the lack of technology and funding. In the conclusions, the main attention is paid to the fact that in the future the evolution of digital technologies will pose new challenges for pedagogical thought and its development.
Keywords: Higher medical education; Digital technologies; Ukraine; Innovation; Optimization